Festa de Sant'Ana e Divino Espírito Santo no terreiro Fé em Deus: as relações do pesquisador no campo - AIRES, Maria do Socorro Rodrigues de Souza (2014)
This study is about the interactions established between researcher and object of study at a yard of Mina's drum in São Luís. The 1 Fé em Deus yard has as religious leader the 2 mãe-de-santo Elzita. The Mina's drum is a kind of denomination for religion of African matrix which was incorporated in Maranhão through Black slavers. The present work intends to analyze the interactions between researcher and object of study in context related to celebrations known as "Senhora Sant'Anna" and "Divino Espírito Santo". At the first moment, we create a draft of self-analysis and discuss about the research development and then, we presented the yard of "Mãe Elzita" to emphasize religious practices in the drums of Mina, Borá and Cura . Then, we create an ethnographic description of the celebrations Senhora Sant'Anna and "Espírito Santo" inside the Fé em Deus" yard, which was supported by means of comments in 2013, as of the calendar of celebrations that place in this period, involving catholics, cultural and religious activities in a great event. In Relations Dynamics and Social Interactions in the context of celebration Senhora Sant'Anna", because our main objective is to analyze our participation as godmother of cake table. In the final considerations, we resumed the issues raised in the work and presented the conclusions about the interactions in relations of the researcher inside search field and we analyze some difficulties experienced in the participant observation inside a yard community of Mina's drum.